Antibiotic Residue- Food Producing Animal Origin and Its Impact on Human Health - Nirala, Ramesh K.; Anjana, K.; Mandal , K. G.; Jayachandran, C. (International Journal of Livestock Research, 2018)
Antibiotics are mainly employed for chemotherapeutic, prophylactic purposes and also used as feed additives to promote growth and improve feed efficiency. However, antibiotic residues in animal products may occur, when administration of drug in extra label fashion and not following of withholding or withdrawal period after treatment. A withdrawal period is established to safeguard human from exposure of antibiotic added food. The withdrawal time is the time required for the residue of toxicological concern to reach safe concentration as defined by tolerance. Many of the administered drugs are not completely absorbed from gut and excreted through faeces and urine as either parent compound or its toxic metabolites. The application of manure or farm effluents in agricultural land leads to selection of resistant bacteria, development and transmission of antibiotic resistance genes in the microbes. The antibiotic resistance in animal and human leads to poor response to treatment during illness. The antibiotic residues in animal product causes harmful effect on health and also interfere with the processing of milk and milk products. The present review focuses on antibiotic residues in animal products and its impact on environments and human health.